Re-Audit on Improving Patients’ Experiences of Ward Round in Psychiatry Wards - Rifat Binte Radwan; Chiro Islam Mallik; Harsha Gopishetty (BJPsych Open)
Aims: The re-audit aims to assess the improvements in patients’ experiences during ward rounds compared with the findings of the original 2022 audit.